Effect Of Internet Addiction On Academic Performance And Mental Health Of Medical Students - Ijaz Ali; Ommia Kalsoom; Syed Asif Jahanzeb Kazmi; Tahir Ahmad Munir; Zanib Qayyum; Naheed Akhter; Athar Ahmad Jan (Journal of Bahria University Medical and Dental College)
Objective: Objective of this study was to determine internet addiction and its impact on mental health and academic performance in medical students. Methodology: One hundred medical students (male: 50, female: 50) aged 18–21 years were selected by convenience sampling in this cross-sectional study in Mahi-ud-din Islamic Medical college Mirpur AJK. A questionnaire of Young’s internet addiction test was used to identify the prevalence of Internet addiction, the purposes of Internet use, and their priority levels. Frequencies and level of mental health was measured using Mental health Battery by Singh and Gupta. Chi square test was applied and p value <0.05 was considered significant. Results: Out of 100 students, 46 (male: 28, female: 18) were found to be slightly addicted, 53 students were average online users and only 01 male was severely addicted. There was no significant difference between male and female students in addiction level. However, males were more addicted than females. The major use of Internet was to communicate with friends and family and to watch songs and movies. 51 students used the Internet to assess information for their educational and learning activities. Some students with overuse of the Internet lead to insufficient sleep and affected their concentration levels in the class. Conclusion: Medical students experiencing problems due to Internet overuse and experiencing poor academic progress and lack of concentration while studying. The main use of the Internet was to communicate with friends and family and for entertainment.